The abundance of microplastics in coral reef ecosystems in the waters of Krueng Raya, Aceh Besar - Ulfah Maria; Juliani Rika; Agustina Sri; Purnawan Syahrul; Malayana Intan; Muliari; Miswari Nur; Yusrizal; Irfannur (BIO Web of Conferences)
The Krueng Raya waters in Aceh Besar, which serve as a habitat for coral reef ecosystems, face the threat of microplastic pollution. This pollution is caused by human activities such as tourism, fishing, and domestic waste, leading to the generation of plastic waste and microplastics. Microplastics have the potential to disrupt the balance of marine ecosystems due to their non-degradable and toxic nature to organisms. This study aims to analyze the abundance and types of microplastics in sediment from coral reef ecosystems at three locations in Krueng Raya waters (Inong Bale, Ahmad Rhang Manyang, and Lhok Mee) and evaluate the correlation between microplastic abundance and live coral conditions. Data were collected in June 2021 using the probability sampling method, which ensures samples are logically and representatively selected from the microplastic population. Microplastic samples were collected around the coral reef area using a PVC pipe with a diameter of 10 cm. Field data were then analyzed in a marine biology laboratory using a microscope, categorizing the microplastics into three types:fragments, fibers, and films. Laboratory analysis showed an average microplastic abundance of 16,67 particles/kg, with fragments being the dominant type. Lhok Mee station exhibited the highest abundance (20,4 particles/kg) due to high levels of human activity. No correlation was found between microplastic abundance and live coral conditions, indicating the need for further research to understand this relationship. These findings underscore the importance of waste management to protect marine ecosystems.